Synthesis and crystal structure of catena-poly[[bis(nitrato-κ2O,O′)strontium(II)]-di-μ-l-histidine-κ3O,O′:O;κ2O:O′] - Sathish Marimuthu; Thangavelu Balakrishnan; M. Judith Percino; Perumal Venkatesan (Acta Crystallographica Section E: Crystallographic Communications, 2025)
The title mono-periodic coordination polymer, [Sr(NO3)2(C6H9N3O2)2]n, was synthesized from L-histidine and strontium nitrate. Crystallizing in the monoclinic space group C2, the structure features an Sr2+ cation (site symmetry 2) coordinated by ten oxygen atoms from zwitterionic L-histidine ligands and nitrate anions, forming a distorted decahedral geometry with Sr—O bond lengths ranging from 2.645 (4) to 2.863 (4) Å. The bridging L-histidine molecules generate a polymeric chain extending along the [010] direction. The structure is consolidated by N—H...O, N—H...N and weak C—H...O hydrogen bonds, creating layers lying parallel to the bc plane.